Milton Friedman: nicht nur ein 'Monetarist'! - Martin Leschke (Wirtschaftsdienst, 2012)
Milton Friedman war einer der größten Ökonomen des letzten Jahrhunderts. Seine intensive Auseinandersetzung mit dem Keynesianismus und seine Gegenthesen haben die ökonomische Wissenschaft gespalten, aber auch vielfältige Diskussionen befördert. Als streitbarer Verfechter der Marktwirtschaft hat er die Wirtschaftswissenschaft nachhaltig beeinflusst. Martin Leschke würdigt das Lebenswerk Milton Friedmans, der Ende Juli 100 Jahre alt geworden wäre. – – Milton Friedman was one of the most prominent advocates of free market economics. Of course, Friedman is popularly recognized for monetarism. His so-called money supply rule and his scepticism of public debt are being rediscussed seriously in the light of the present crises. But Friedman was more than a monetarist. His famous thesis 'The Social Responsibility of Business is to Increase its Profits' caused a heated debate that continues today. In a similar way Friedman initiated a controversial discussion by introducing an argument in support of unrealistic assumptions (in his essay 'The Methodology of Positive Economics'). Furthermore, his very clear and concrete proposals to promote a liberal society will be remembered long after his death.
Keywords: E5; B41; 330; Monetarismus; Dogmengeschichte